DECOLONIZING CANCER CARE IN CANADA. (December 2021) - Beckett, Matthew; Cole, Katherine; White, Mitchell; Chan, Jessica; McVicar, Jason; Rodin, Danielle; Clemons, Mark; Bourque, Jean-Marc
Highlights: Cancer incidence and mortality in Indigenous peoples of Canada are increasing These populations face modifiable risk factors and lack of access to care Indigenous cancer care has been jurisdictionally complex and ambiguous Successful initiatives must be locally contextualized, with Indigenous leadership Abstract: Cancer incidence and mortality among Indigenous peoples of Canada (First Nations, Inuit, and Métis) continue to rise in contrast to non-Indigenous Canadians, and Indigenous peoples are at higher risk of cancers associated with known modifiable risk factors. Jurisdictional and administrative challenges have hindered high quality cancer care for Indigenous peoples since the country's inception, and different Indigenous populations face these challenges under similar yet non-identical circumstances. Collaborative initiatives under Indigenous leadership have drawn attention to specific issues such as screening, funding, and culturally appropriate care, and have identified resources necessary to address these problems. The Canadian Partnership Against Cancer and their collaborators have committed significant resources to Indigenous cancer programs with locally and regionally determined leadership and priorities. In the context of broader global movements against systemic racism and inequity, decolonization of cancer care demands critical analysis of the existing cancer systems and restructuring under Indigenous leadership with multidisciplinary collaboration.